An Overview of the “Vento Norte” Experiment (VNorEx): Observations of Downslope Windstorms over Modest Terrain in Southern Brazil - Michel Stefanello; Murilo M. Lopes; Eberton C. De Souza; Mateus S. Rebelo; Daniel C. Santos; Tamíres Zimmer; Cinara E. Da Rosa; Rafael Santana; João A. V. Da Silva; Hector V. B. Da Rosa; Richard Lobato; Beatriz F. Mota; et al. (Advances in Atmospheric Sciences, 2026)

Differential drought tolerance in two commercial açaí cultivars: Insights from gas exchange, chlorophyll fluorescence, and antioxidant responses - Patricia C. A. Navegantes; Wagner Romulo L. Lopes Filho; Flavio Henrique S. Rodrigues; Rosane Patricia F. Chaves; Roberto L. Cunha; Lucas C. Costa; Hugo A. Pinheiro (Trees, 2026)

Predictive validation of the repeated low-dose reserpine rodent model of parkinsonism - Vinicius Bioni; Alvaro C. Lima; Debora M. G. Cunha; Narriman Gonçalves; Leonardo B. Lopes-Silva; João P. Kurita; Manuela B. L. Soares; Marcela Becegato; Aline C. Ramos; Anderson H. F. F. Leão; Regina H. Silva (Experimental Brain Research, 2026)
L-DOPA (LD) is the gold-standard treatment of motor symptoms in Parkinson’s disease (PD), conventionally used to prove the predictive value of PD animal models. This study aimed to investigate the predictive validity of an adaptation of the conventional reserpine model of PD: the repeated low-dose reserpine administration in rodents, which promotes progressive motor impairment in catalepsy, vacuous chewing behavior tests, and neurochemical deficits. Specifically, we investigated the effects of acute and chronic treatment with LD on motor alterations induced in mice by this modified protocol. Swiss mice were treated with 20 reserpine injections (0.1 mg/kg, s.c., every other day). Acute LD (25, 50, 100, and 200 mg/kg) administration was performed at the end of reserpine protocol to assess immediate motor recovery. Additionally, concomitant chronic LD (50 and 100 mg/kg) treatment was conducted to investigate potential attenuation of motor impairment and dopamine depletion quantified by HPLC. Repeated reserpine protocol induced motor deficits in catalepsy and vacuous chewing evaluations and striatal dopamine depletion. Acute LD administration significantly improved catalepsy in higher doses, while chronic LD treatment attenuated motor impairments and reduced dopamine depletion in the striatum. These findings support the predictive validity of the reserpine rodent model for studying parkinsonism. Together with the ability to promote chronic and progressive parkinsonian alterations, the reversion of these deficits by LD reinforces the potential of the repeated low-dose reserpine protocol for studies of potential therapies and the pathophysiology underlying neurodegenerative processes in PD.

Assessment of protein incorporation into SBA-15 particles and their structural changes - Jessica A. F. Pedro; Luis C. Cides-da-Silva; Tereza S. Martins; Marcia C. A. Fantini; Jose L. S. Lopes (European Biophysics Journal, 2026)

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Prospection of Autochthonous Lactic Acid Bacteria Displaying Probiotic Potential to Enhance Colossoma macropomum Larvae Growth and Immunoprotection Against Aeromonas hydrophila - Thayná M. dos Santos; Layana A. B. Pereira; Laine P. C. dos Santos; Andrya L. Lopes; Larissa A. F. Sampaio; Graziella V. G. de Matos Silva; Juliana N. Ferreira; Gleika T. J. Dos Reis; Jonny B. Teixeira; Raimundo J. T. Diniz‐Neto; Laura G. M. de Carvalho; Michelle Midori Sena Fugimura; et al. (Journal of Fish Diseases, 2026)
This study assessed the functional potential of autochthonous lactic acid bacteria isolated from the gastrointestinal tract of tambaqui ( Colossoma macropomum ) as larviculture probiotics. Five strains were selected and identified as belonging to the genus Weissella . In vitro assays revealed high tolerance to acidic pH (2.0–3.0), resistance to bile salts (10%), biofilm formation capacity, hydrophobicity and direct Aeromonas hydrophila inhibition. In in vivo tests, strains M13 and M14 promoted significant increases in tambaqui survival (72.2% and 68.7%; p

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Removing pollutants and recovering resources in treatment wetlands cultivated with ora-pro-nobis and citronella - L. S. Lopes; T. S. Alves; A. M. Araújo; F. F. Cunha; A. P. Rosa; A. C. Borges (International Journal of Environmental Science and Technology, 2025)

Novel phenanthroline-based ruthenium complex as a promising antimicrobial agent - Pedro L. N. Teixeira; Ana C. S. Gondim; Tercio F. Paulo; Eduardo H. S. Sousa; Luiz G. F. Lopes; Alejandro P. Ayala; Ellen A. Malveira; Edson H. Teixeira; Mayron A. Vasconcelos; Alda K. M. Holanda (JBIC Journal of Biological Inorganic Chemistry, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Characterizing pioneer plants for phytoremediation of mercury-contaminated urban soils - C. dos Santos Soares; V. J. Santos Lopes; F. de Freitas; M. O. Córdova; L. Cavalheiro; L. D. Battirola; R. L. T. de Andrade (International Journal of Environmental Science and Technology, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Identification of pearl millet as a major host of Leptodelphax maculigera (Hemiptera: Delphacidae), a potential vector of plant viruses - Euclides S. Vilanova; Ana J. Zuin; Leonardo C. Spada; Joyce A. Froza; Gabriel L. F. Mejdalani; João R. S. Lopes (Journal of Plant Diseases and Protection, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Conventional environmental assessments are inadequate for predicting and mitigating impacts of dams on migratory fish in Brazil: an integrative assessment approach for the Neotropics - J. M. Lopes; A. Peressin; F. R. de Andrade; M. F. Moreira; S. Ludwig; J. S. M. Pimentel; L. Wouters; I. G. Prado; F. M. Suzuki; C. B. M. Alves; P. S. Pompeu (Aquatic Sciences, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A biofloc system avoids the adverse effects of diets with suboptimal protein levels on zootechnical performance, intestinal histomorphometry, and protein metabolism of Nile tilapia juvenile fed Spirulina biomass (Arthrospira platensis) as an alternative protein source - Fernanda Picoli; Alana D. de Oliveira; Suelyn O. Marques; Deise C. Terhorst; Suélen Serafini; Luísa Nora; Fabio F. Neves; Maurício G. C. Emerenciano; Diogo L. A. Lopes; Aleksandro S. da Silva; Thiago E. H. P. Fabregat (Fish Physiology and Biochemistry, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Freezing and thawing in Antarctica: characterization of antifreeze protein (AFP) producing microorganisms isolated from King George Island, Antarctica - J. C. Lopes; V. P. Veiga; B. Seminiuk; L. O. F. Santos; A. M. C. Luiz; C. A. Fernandes; C. T. Kinasz; V. H. Pellizari; R. T. D. Duarte (Brazilian Journal of Microbiology, 2024)

Sleep deprivation induces late deleterious effects in a pharmacological model of Parkinsonism - L. B. Lopes-Silva; D. M. G. Cunha; A. C. Lima; V. S. Bioni; N. Gonçalves; J. P. F. Kurita; R. Wuo-Silva; R. H. Silva (Experimental Brain Research, 2024)

Repeated water deficit events trigger adjustments in enzymatic antioxidant system in oil palm - Wagner Romulo L. Lopes Filho; Flavio Henrique S. Rodrigues; Rosane Patrícia F. Chaves; Roberto L. Cunha; Lucas C. Costa; Hugo A. Pinheiro (Theoretical and Experimental Plant Physiology, 2024)

Complexities of reef fisheries in Brazil: a retrospective and functional approach - Linda Eggertsen; André L. Luza; César A. M. M. Cordeiro; Cristian Dambros; Carlos E. L. Ferreira; Sergio R. Floeter; Ronaldo B. Francini-Filho; Kátia M. F. Freire; Maria A. Gasalla; Tommaso Giarrizzo; Vinicius J. Giglio; Natalia Hanazaki; et al. (Reviews in Fish Biology and Fisheries, 2024)

Enhancing the taxonomic delimitation of Lippia origanoides Kunth (Verbenaceae) by analyzing volatile terpenes and molecular markers in micropropagated accessions - Laís M. Frattini; Arthur A. Oliveira; Jhoão S. Kotsubo; Íris B. Gorne; Isabel C. Silva; Jober C. E. Freitas; Cristiano F. Resende; Ana C. Mezzonato-Pires; Elyabe M. Matos; Juliana M. L. Lopes; Lyderson F. Viccini; Richard M. Grazul; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Tarballs on the Brazilian coast in late 2022 sustain Lepas anatifera Linnaeus, 1758 (Crustacea: Cirripedia): Occurrence and risk of petroleum hydrocarbon ingestion - Luiza C. Mello; Adriana P. Nascimento; Beatriz D. Lopes; Antônia D.F. Lima; Luís E.A. Bezerra; Liana de F. Mendes; Luciana M. Bastos; Arlene B.S. Nossol; Mário M. Martins; Laercio L. Martins; Rivelino M. Cavalcante (Science of The Total Environment, 2023)

Effect of the racial group and body condition score at calving on production performance and metabolic profile of buffaloes during the transition period - R. D. G.e Silva; M. V. G. Loiola; A. L. Ribeiro Filho; D. C. Cotrim; B. S. dos Santos Rekowsky; I. M. S. Lopes; L. F. de A. Bulcão; M. L. G. M. L. de Araújo; D. dos S. Pina; G. G. P. de Carvalho; J. E. de Freitas (Tropical Animal Health and Production, 2023)

International Lima Bean Network: from the origin of the species to modern plant breeding - Jaime Martínez-Castillo; Ademir S. F. Araujo; María I. Chacón-Sánchez; Luis G. Santos; Angela C. A. Lopes; Kimberly Gibson; Regina L. F. Gomes; Rubén H. Andueza-Noh; Elena Bitochi; Horacio S. Ballina-Gómez; Eduardo Peralta; Ernesto Ormeño-Orrillo; et al. (Genetic Resources and Crop Evolution, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

Toxicity of fipronil and 2,4-D pesticides in Daphnia similis: a multiple endpoint approach - Natália C. Gallo; Laís F. P. Lopes; Cassiana C. Montagner; Evaldo L. G. Espíndola; Raquel A. Moreira (Environmental Science and Pollution Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Structural analysis of the peptides temporin-Ra and temporin-Rb and interactions with model membranes - José L. S. Lopes; Caio C. F. Araujo; Rogério C. Neves; Jochen Bürck; Sheila G. Couto (European Biophysics Journal, 2022)

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Influence of Nitric Oxide–Cyclic GMP and Oxidative STRESS on Amyloid-β Peptide Induced Decrease of Na,K-ATPase Activity in Rat Hippocampal Slices - E. M. Kawamoto; M. M. Cararo-Lopes; P. F. Kinoshita; L. E. M. Quintas; L. S. Lima; D. Z. Andreotti; C. Scavone (The Journal of Membrane Biology, 2021)

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Influence of Urban Landscape on Ants and Spiders Richness and Composition in Forests - T S Melo; E F Moreira; M V A Lopes; A R S Andrade; A D Brescovit; M C L Peres; J H C Delabie (Neotropical Entomology, 2021)

Correction to: α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Acute and chronic toxicity of 2,4-D and fipronil formulations (individually and in mixture) to the Neotropical cladoceran Ceriodaphnia silvestrii - Laís C. M. Silva; Raquel A. Moreira; Thandy J. S. Pinto; Allan P. Ogura; Maria P. C. Yoshii; Laís F. P. Lopes; Cassiana C. Montagner; Bianca V. Goulart; Michiel A. Daam; Evaldo L. G. Espíndola (Ecotoxicology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Longitudinal Study of Foraging Networks in the Grass-Cutting Ant Atta capiguara Gonçalves, 1944 - N. Caldato; R. Camargo; K. K. Sousa; L. C. Forti; J. F. Lopes; V. Fourcassié (Neotropical Entomology, 2020)

Urban wild meat consumption and trade in central Amazonia - Hani R. El Bizri; Thaís Q. Morcatty; João Valsecchi; Pedro Mayor; Jéssica E. S. Ribeiro; Carlos F. A. Vasconcelos Neto; Jéssica S. Oliveira; Keilla M. Furtado; Urânia C. Ferreira; Carlos F. S. Miranda; Ciclene H. Silva; Valdinei L. Lopes; et al. (Conservation Biology, 2020)
The switch from hunting wild meat for home consumption to supplying more lucrative city markets in Amazonia can adversely affect some game species. Despite this, information on the amounts of wild meat eaten in Amazonian cities is still limited. We estimated wild meat consumption rates in 5 cities in the State of Amazonas in Brazil through 1046 door‐to‐door household interviews conducted from 2004 to 2012. With these data, we modeled the relationship between wild meat use and a selection of socioeconomic indices. We then scaled up our model to determine the amounts of wild meat likely to be consumed annually in the 62 urban centers in central Amazonia. A total of 80.3% of all interviewees reported consuming wild meat during an average of 29.3 (CI 11.6) days per year. Most wild meat was reported as bought in local markets (80.1%) or hunted by a family member (14.9%). Twenty‐one taxa were cited as consumed, mostly mammals (71.6%), followed by reptiles (23.2%) and then birds (5.2%). The declared frequency of wild meat consumption was positively correlated with the proportion of rural population as well as with the per capita gross domestic product of the municipality (administrative divisions) where the cities were seated. We estimated that as much as 10,691 t of wild meat might be consumed annually in the 62 urban centers within central Amazonia, the equivalent of 6.49 kg per person per year. In monetary terms, this amounts to US$21.72 per person per year or US$35.1 million overall, the latter figure is comparable to fish and timber production in the region. Given this magnitude of wild meat trade in central Amazonia, it is fundamental to integrate this activity into the formal economy and actively develop policies that allow the trade of more resilient taxa and restrict trade in species sensitive to hunting.

Marker-assisted selection in Gossypium spp. for Meloidogyne incognita resistance and histopathological characterization of a near immune line - C. M. L. Lopes; N. D. Suassuna; J. E. Cares; A. C. M. M. Gomes; F. J. Perina; G. F. Nascimento; J. S. F. Mendonça; A. W. Moita; R. M. D. G. Carneiro (Euphytica, 2020)

Artemisia annua L. and photoresponse: from artemisinin accumulation, volatile profile and anatomical modifications to gene expression - Ellen M. Lopes; Fábia Guimarães-Dias; Thália do S. S. Gama; Arthur L. Macedo; Alessandra L. Valverde; Marcela C. de Moraes; Ana Cristina A. de Aguiar-Dias; Humberto R. Bizzo; Marcio Alves-Ferreira; Eliana S. Tavares; Andrea F. Macedo (Plant Cell Reports, 2020)

Structure-based design of δ-lactones for new antifungal drug development: susceptibility, mechanism of action, and toxicity - Daiane F. Dalla Lana; Ânderson R. Carvalho; William Lopes; Marilene H. Vainstein; Luciano S. P. Guimarães; Mário L. Teixeira; Luis F. S. de Oliveira; Michel M. Machado; Saulo F. de Andrade; Marcus M. Sá; Theo V. C. Russo; Gustavo P. Silveira; et al. (Folia Microbiologica, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Regeneration of Diabetic Foot Ulcers Based on Therapy with Red LED Light and a Natural Latex Biomembrane - S. S. R. F. Rosa; M. F. F. Rosa; M. P. Marques; G. A. Guimarães; B. C. Motta; Y. C. L. Macedo; P. Inazawa; A. Dominguez; F. S. Macedo; C. A. P. Lopes; A. F. da Rocha (Annals of Biomedical Engineering, 2019)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Ticks (Acari: Ixodidae) of the state of Amazonas, Brazil - Sergio L. Gianizella; Thiago F. Martins; Valeria C. Onofrio; Nair O. Aguiar; Waleska Gravena; Carlos A. R. do Nascimento; Laérzio C. Neto; Diogo L. Faria; Natália A. S. Lima; Monica R. Solorio; Louise Maranhão; Ivan J. Lima; et al. (Experimental and Applied Acarology, 2018)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

Prevalence of hypertension and its associated factors in contaminated areas of the Santos-São Vicente Estuarine region and Bertioga, Brazil: 2006-2009 - T. S. Ribeiro; D. P. Carvalho; M. T. Guimarães; N. N. Campina; M. R. Lobarinhas; A. L. J. Lopes; M. G. Cunha; I. B. Souza; V. L. F. Oliveira; L. C. Martins; A. Gomes; L. A. A. Pereira; et al. (Environmental Science and Pollution Research, 2016)

Freshwater vertebrate metabarcoding on Illumina platforms using double-indexed primers of the mitochondrial 16S rRNA gene - Miguel Vences; Mariana L. Lyra; R. G. Bina Perl; Molly C. Bletz; David Stanković; Carla Martins Lopes; Michael Jarek; Sabin Bhuju; Robert Geffers; Célio F. B. Haddad; Sebastian Steinfartz (Conservation Genetics Resources, 2016)

Foraging activity pattern and herbivory rates of the grass-cutting ant Atta capiguara - N. Caldato; L. C. Forti; S. Bouchebti; J. F. S. Lopes; V. Fourcassié (Insectes Sociaux, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Community structure of resting egg banks and concordance patterns between dormant and active zooplankters in tropical lakes - Jayme M. Santangelo; Paloma M. Lopes; Monalisa O. Nascimento; Ana Paula C. Fernandes; Sandra Bartole; Marcos P. Figueiredo-Barros; João J. F. Leal; Francisco A. Esteves; Vinicius F. Farjalla; Claudia C. Bonecker; Reinaldo L. Bozelli (Hydrobiologia, 2015)

Prevalence of liver diseases as referred by people living in the Santos and São Vicente Estuary - Daniele Fernandes Pena Carvalho; M. T. Guimarães; T. S. Ribeiro; N. N. Campina; M. R. Lobarinhas; A. L. J Lopes; M. G. Cunha; I. B. Souza; V. L. F. Oliveira; L. Braga E Braga; L. C. Martins; A. Gomes; et al. (Environmental Science and Pollution Research, 2015)

Use of Seeds as Fungus Garden Substrate Changes the Organization of Labor Among Leaf-Cutting Ant Workers - I N Hastenreiter; T A Sales; R S Camargo; L C Forti; J F S Lopes (Neotropical Entomology, 2015)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Types of Degradation, Causes, and Implications for Management - Or. Kairis; C. Kosmas; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Methodological Approach - C. Kosmas; Or. Kairis; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

Science Education in a Museum: Enhancing Earth Sciences Literacy as a Way to Enhance Public Awareness of Geological Heritage - J. Reis; L. Póvoas; F. J. A. S. Barriga; C. Lopes; V. F. Santos; B. Ribeiro; J. Cascalho; A. Pinto (Geoheritage, 2014)

Erratum to: Ureaplasma diversum as a cause of pustular vulvovaginitis in bovine females in Vale Guapore, Mato Grosso State, Brazil - João Guilherme L. N. Gaeti; Marconni V. C. Lana; Gustavo S. Silva; Leticya L. Lopes; Camila G. de Campos; Fernanda H. Maruyama; Edson M. Colodel; Eduardo F. Costa; Luis G. Corbellini; Luciano Nakazato; Caroline A. Pescador (Tropical Animal Health and Production, 2014)

Discrimination of the Acinetobacter calcoaceticus–Acinetobacter baumannii complex species by Fourier transform infrared spectroscopy - C. Sousa; L. Silva; F. Grosso; A. Nemec; J. Lopes; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Mercury in Indigenous, Introduced and Farmed Fish from the Semiarid Region of the Jaguaribe River Basin, NE Brazil - L. D. Lacerda; B. G. B. C. Costa; D. N. Lopes; K. Oliveira; M. F. Bezerra; W. R. Bastos (Bulletin of Environmental Contamination and Toxicology, 2014)

Identification of potential leafhoppers vectors of phytoplasmas (16SrIII group) associated with broccoli stunt disease in Brazil - B. Eckstein; J. C. Barbosa; P. F. Kreyci; K. M. R. Zanol; L. B. N. Coelho; A. C. S. M. L. Gonçalves; K. R. Brunelli; J. R. S. Lopes; I. P. Bedendo (Australasian Plant Pathology, 2014)

Seed structure, germination, and reserve mobilization in Butia capitata (Arecaceae) - N. C. C. Oliveira; P. S. N. Lopes; L. M. Ribeiro; M. O. Mercandante-Simões; L. A. A. Oliveira; F. O. Silvério (Trees, 2013)

Natural regeneration of the herbaceous community in a semiarid region in Northeastern Brazil - J. M. F. F. Santos; D. M. Santos; C. G. R. Lopes; K. A. Silva; E. V. S. B. Sampaio; E. L. Araújo (Environmental Monitoring and Assessment, 2013)

Selenium, Chromium and Cobalt Diffusion into Mangrove Sediments: Radiotracer Experiment Evidence of Coupled Effects of Bioturbation and Rhizosphere - Katia N. Suzuki; E. C. Machado; W. Machado; A. V. B. Bellido; L. F. Bellido; J. A. Osso; R. T. Lopes (Water, Air, & Soil Pollution, 2012)

Ecological determinism increases with organism size - Vinicius F. Farjalla; Diane S. Srivastava; Nicholas A. C. Marino; Fernanda D. Azevedo; Viviane Dib; Paloma M. Lopes; Alexandre S. Rosado; Reinaldo L. Bozelli; Francisco A. Esteves (Ecology, 2012)
After much debate, there is an emerging consensus that the composition of many ecological communities is determined both by species traits, as proposed by niche theory, as well as by chance events. A critical question for ecology is, therefore, which attributes of species predict the dominance of deterministic or stochastic processes. We outline two hypotheses by which organism size could determine which processes structure ecological communities, and we test these hypotheses by comparing the community structure in bromeliad phytotelmata of three groups of organisms (bacteria, zooplankton, and macroinvertebrates) that encompass a 10 000‐fold gradient in body size, but live in the same habitat. Bacteria had no habitat associations, as would be expected from trait‐neutral stochastic processes, but still showed exclusion among species pairs, as would be expected from niche‐based processes. Macroinvertebrates had strong habitat and species associations, indicating niche‐based processes. Zooplankton, with body size between bacteria and macroinvertebrates, showed intermediate habitat associations. We concluded that a key niche process, habitat filtering, strengthened with organism size, possibly because larger organisms are both less plastic in their fundamental niches and more able to be selective in dispersal. These results suggest that the relative importance of deterministic and stochastic processes may be predictable from organism size.

Evaluation of Chlorine Decay in Drinking Water Systems for Different Flow Conditions: From Theory to Practice - Helena M. Ramos; D. Loureiro; A. Lopes; C. Fernandes; D. Covas; L. F. Reis; M. C. Cunha (Water Resources Management, 2010)

Nest architecture of the leaf-cutting ant Acromyrmex rugosus rugosus - S. S. Verza; L. C. Forti; J. F. S. Lopes; W. O. H. Hughes (Insectes Sociaux, 2007)

Larval isolation and brood care in Acromyrmex leaf-cutting ants - J. F. S. Lopes; W. O. H. Hughes; R. S. Camargo; L. C. Forti (Insectes Sociaux, 2005)

Evidence that arachidonic acid derived from neutrophils and prostaglandin E2 are associated with the induction of acute lung inflammation by lipopolysaccharide of Escherichia coli - T. C. Alba-Loureiro; E. F. Martins; C. K. Miyasaka; L. R. Lopes; R. G. Landgraf; S. Jancar; R. Curi; P. Sannomiya (Inflammation Research, 2004)

The Marine Mussel Perna perna (Mollusca, Bivalvia, Mytilidae) as an Indicator of Contamination by Heavy Metals in the Ubatuba Bay, SÃo Paulo, Brazil - W. E. P. Avelar; F. L. M. Mantelatto; A. C. Tomazelli; D. M. L. Silva; T. Shuhama; J. L. C. Lopes (Water, Air, & Soil Pollution, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)